ANALYSIS OF THE THREAT OF THE SPREAD OF INTIMATE CONTENT NON CONSENSUAL IN VIOLENCE GENDER BASED ONLINE - Prayudati, Yulia Martha; Trisna, Wessy; Sharfina Desiandri, Yati (Penerbit Lafadz Jaya, 2025)
This journal discusses the phenomenon of Online Gender-Based Violence (OGBV) which is increasingly worrying in the digital era, especially related to the spread of non-consensual intimate content (NCII) or what is often referred to as